2004
DOI: 10.1039/b304116f
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of nanostructured metal films

Abstract: Nanostructured metal films of platinum, gold and silver up to 675 nm thick we prepared by electrochemical deposition through templates of 700 nm diameter polystyrene spheres assembled as hexagonal close packed monolayer on an evaporated gold surface followed by removal of the template by dissolution in tetrahydrofuran. The reflection spectra of the films at normal incidence were recorded as a function of film thickness and the spectra correlated with the local visual appearance of the film and the surface stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
201
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(207 citation statements)
references
References 74 publications
(108 reference statements)
5
201
1
Order By: Relevance
“…After deposition the polystyrene was removed to leave the thin structured gold films containing a regular hexagonal array of uniform segment sphere voids. These surfaces are strongly coloured, the precise colour depending on the viewing angle, void diameter and film thickness [18]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After deposition the polystyrene was removed to leave the thin structured gold films containing a regular hexagonal array of uniform segment sphere voids. These surfaces are strongly coloured, the precise colour depending on the viewing angle, void diameter and film thickness [18]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 shows SEM images of structured gold surfaces and an electrochemically roughened gold surface. The structured gold films have different thicknesses and were produced by electrochemical deposition through templates consisting of a monolayer of 600 nm diameter polystyrene spheres [18]. The mouths of the pores are nearly circular and their diameter changes with the film thickness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substrates were prepared following the previously published method of Bartlett et al 27 Substrates were prepared by templated electrodeposition on flat, conductive surfaces prepared by thermal vapour deposition of a 10 nm layer of chromium, followed by 200 nm of gold, onto glass slides. These gold surfaces were treated with a 10 mM ethanolic solution of cysteamine for at least 48 h before use.…”
Section: Preparation Of Structured Substratesmentioning
confidence: 99%
“…21,28 Hence, it was chosen for the study reported in this paper. The film heights are as estimated from the pore-mouth diameters of the voids determined by examining their SEM images.w The method has been earlier described by Bartlett et al 27 Surface immobilization of molecules After cleaning, the substrates were dipped in an ethanolic solution of cysteamine (10 mM) for 24 h. The substrates were then washed and dried under argon. We used the well-known chemistry of N-hydroxysuccinamide esters (NHS esters) employed in immobilizing biomolecules.…”
Section: Preparation Of Structured Substratesmentioning
confidence: 99%